Religious Development of Children with Special Needs in Inclusion Classes (Case Study at Al Irsyad 02 Elementary School Cilacap) - Toifur, Toifur; Priyanto, Dwi; Azmi Nuraziz, Muhammad (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aims to describe and analyze the development of religious diversity of children with special needs in the inclusion class. This type of research is field research with a qualitative approach. The subjects of this study are classroom teachers, school principals, Islamic Religious Education teachers, inclusion coordinators, and special assistant teachers. The selection of research subjects used the purposive sampling technique. Data collection was carried out using observation, interview, and documentation techniques. The data analysis technique used is qualitative descriptive with stages of data reduction, data display, and conclusion. The results of the study show that the development of religious diversity for children with special needs is carried out by Islamic Religious Education teachers supported by the BLC (Butterfly Learning Center) team. The development of religious diversity for children with special needs is carried out using a pull-out learning model. The pull out learning model was carried out in the BLC room by the BLC team. The development of religious diversity for children with special needs is more emphasized on the aspects of morality and worship